Vocabulary knowledge in science learning on children’s development through farming activities in the rural area - Hashim, Mega Suria; Said, Ismail (Southeast Asia Early Childhood Journal, 2021)
Outdoor activities can harness children’s personal and social abilities differently than could indoor activities. Children experience a variety of words associated with science learning through smelling, feeling, and tasting. The direct contact with nature and vegetation is the point where children’s communication ability is harnessed as they begin to use proper vocabulary. Yet, they are less educated on the importance of appropriate vocabulary learning, particularly using scientific vocabulary when confronted with the outdoor environment. Therefore, this study aims to identify children’s vocabulary knowledge on science learning towards supporting their personality development through hands-on engagement with farming activities. Ten children of aged 6-12 years old were recruited for a programme in a rural area at Laman Tamara, Kg. Sikai, Negeri Sembilan, Malaysia. They were observed for changes in their vocabulary using hands-on techniques. Data on their hands-on approaches and perceptions w ere elicited from a participatory behavioural approach, photo-taking, and interviews. Content analysis of the data was performed using Nvivo 12 Plus. The results indicated that the children developed a greater emotional affinity from the various hands-on approaches through specific vocabulary such as feel, activities, soil, vegetables and farming when dealing with life experiences. They were observed to possess good vocabulary following the high correlation between listening, reading, speaking, and writing. Their perceptions of their knowledge and vocabulary strategies were congruent with their content achievements. These findings align with early childhood education development and growth, such as teachers, playmakers, and parents. Such could expand the quality of science learning on the correct path to be skilled lifelong learners.